Fundamentals of database systems - Elmasri, Ramez; Shamkant B. Navathe (Boston, Massachusetts : Pearson-Addison-Wesley, 2011)
Clear explanations of theory and design, broad coverage of models and real systems, and an up-to-date introduction to modern database technologies result in a leading introduction to database systems. Intended for computer science majors, Fundamentals of Database Systems, 6/e emphasizes math models, design issues, relational algebra, and relational calculus. A lab manual and problems give students opportunities to practice the fundamentals of design and implementation. Real-world examples serve as engaging, practical illustrations of database concepts. The Sixth Edition maintains its coverage of the most popular database topics, including SQL, security, and data mining, and features increased emphasis on XML and semi-structured data.
Part 1. Introduction to Databases -- Chapter 1. Databases and Database Users -- Chapter 2. Database System Concepts and Architecture -- Part 2. The Relational Data Model and SQL -- Chapter 3. The Relational Data Model and Relational Database Constraints -- Chapter 4. Basic SQL -- Chapter 5. More SQL: Complex Queries, Triggers, Views and Schema Modification -- Chapter 6. The Relational Algebra and Relational Calculus -- Part 3: Conceptual Modeling and Database Design -- Chapter 7. Data Modeling Using the Entity-Relationship (ER) Model -- Chapter 8. The Enhanced Entity-Relationship (EER) Model -- Chapter 9. Relational Database Design by ER- And EER-to-Relational Mapping -- Chapter 10. Practical Database Design Methodology and Use of UML Diagrams -- Part 4. Object, Object-Relational, and XML: Concepts, Models, Languages and Standards -- Chapter 11. Object and Object-Relational Databases -- Chapter 12. XML: Extensible Markup Language -- Part 5. Database Programming Techniques -- Chapter 13. Introduction to SQL Programming Techniques -- Chapter 14. Web Database Programming Using PHP -- Part 6. Database Design Theory and Normalization -- Chapter 15. Basics of Functional Dependencies and Normalization for Relational Databases -- Chapter 16. Relational Database Design Algorithms and Further Dependencies -- Part 7. File Structures, Indexing and Hashing -- Chapter 17. Disk Storage, Basic File Structures and Hashing -- Chapter 18. Indexing Structures for Files -- Part 8. Query Processing and Optimization, and Database Tuning --Chapter 19. Algorithms for Query Processing and Optimization -- Chapter 20. Physical Database Design and Tuning -- Part 9. Transaction Processing, Concurrency Control, and Recovery -- Chapter 21. Introduction to Transaction Processing Concepts and Theory -- Chapter 22. Concurrency Control Techniques -- Chapter 23. Database Recovery Techniques -- Part 10. Additional Database Topics: Security and Distribution -- Chapter 24. Database Security -- Chapter 25. Distributed Databases -- Part 11. Advanced Database Models, Systems, and Applications -- Chapter 26. Enhanced Data Models for Advanced Applications -- Chapter 27. Introduction to Information Retrieval and Web Search -- Chapter 28. Data Mining Concepts -- Chapter 29. Overview of Data Warehousing and OLAP.
Includes bibliographical references and index.
Keywords: DATABASE MANAGEMENT